"Competitive" Output in Bilateral Monopoly: Comment - Fellner, WIlliam (Quarterly Journal of Economics, 1950)
“Competitive” Output in Bilateral Monopoly Get access William Fellner William Fellner University of California, Berkeley Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 64, Issue 4, November 1950, Pages 648–650, https://doi.org/10.2307/1884395 Published: 01 November 1950